2020
DOI: 10.1002/glia.23912
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 and DeltaB maintain Müller glia quiescence and act as negative regulators of regeneration in the light‐damaged zebrafish retina

Abstract: Damage to the zebrafish retina stimulates resident Müller glia to reprogram, reenter the cell cycle, divide asymmetrically, and produce neuronal progenitor cells that amplify and differentiate into the lost neurons. The transition from quiescent to proliferative Müller glia involves both positive and negative regulators. We previously demonstrated that the Notch signaling pathway represses retinal regeneration by maintaining Müller glia quiescence in zebrafish. Here we examine which Notch receptor is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 78 publications
5
72
4
Order By: Relevance
“…CRISPR-mediated dll4 gene editing had no significant effect on retinal cell death (Figure 5i). Finally, forced expression of Dll4 with heat shock in hsp70:dll4-P2A-GFP transgenic fish inhibited injury-dependent proliferation of MG-derived progenitors without affecting (Campbell et al 2021). Consistent with this result, we found that Notch3 knockdown with a translation-blocking MO that successfully suppressed chimeric notch3-GFP RNA expression increased the number of MG recruited to a regenerative response as indicated by an expanded zone of injuryresponsive MG (Figure 5-figure supplement 6a-e).…”
Section: Dlb Dll4 and Notch3 Regulate Mg's Response Threshold To Retsupporting
confidence: 78%
See 4 more Smart Citations
“…CRISPR-mediated dll4 gene editing had no significant effect on retinal cell death (Figure 5i). Finally, forced expression of Dll4 with heat shock in hsp70:dll4-P2A-GFP transgenic fish inhibited injury-dependent proliferation of MG-derived progenitors without affecting (Campbell et al 2021). Consistent with this result, we found that Notch3 knockdown with a translation-blocking MO that successfully suppressed chimeric notch3-GFP RNA expression increased the number of MG recruited to a regenerative response as indicated by an expanded zone of injuryresponsive MG (Figure 5-figure supplement 6a-e).…”
Section: Dlb Dll4 and Notch3 Regulate Mg's Response Threshold To Retsupporting
confidence: 78%
“…Like that observed for radial glial stem cells, Notch signaling must be suppressed for MG proliferation and retina regeneration (Campbell et al 2021, Conner et al 2014, Elsaeidi et al 2018, Wan & Goldman 2017, Wan et al 2012). Furthermore, pan-retinal Notch inhibition increases the number of MG that engage in a regenerative response in light and needle poke injury models(Campbell et al 2021, Wan & Goldman 2017, Wan et al 2012), and Notch inhibition enhances spontaneous MG proliferation in uninjured retinas treated with growth factors, cytokines, or forced expression of Ascl1a and Lin28a(Conner et al 2014, Elsaeidi et al 2018, Wan & Goldman 2017).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations